Socioeconomic Impacts of COVID-19 on Households in Somalia : Results from Round 1 of the Somali High-Frequency Phone Survey - Karamba, Wendy (World Bank, Washington, DC, 2021)
The coronavirus disease 2019 (COVID-19) pandemic and its effects on households create an urgent need for timely data and evidence to help monitor and mitigate the social and economic impacts of the crisis on the Somali people, especially the poor and most vulnerable. To monitor the socioeconomic impacts of the COVID-19 pandemic and inform policy responses and interventions, the World Bank designed and conducted a nationally representative Somali High-Frequency Phone Survey (SHFPS) of households. The survey covers important and relevant topics, including knowledge of COVID-19 and adoption of preventative behavior, economic activity and income sources, access to basic goods and services, exposure to shocks and coping mechanisms, and access to social assistance. This brief summarizes the findings of the first round of the SHFPS, implemented between June and July 2020. The information presented here is based on a sample of 2,811 households across all regions of Somalia, drawn using a random digit dialing protocol. Sampling weights are computed to ensure representativeness at the national and state level, and by population type. The same households will be tracked over 12 months, with selected respondents—typically the household head—completing interviews every 8-12 weeks. Monitoring the well-being of households over time will improve understanding of the effects of, and household responses to the COVID-19 pandemic in near-real time.